Harmonic Modeling Methods for Power Electronic Converters: Case study and Comparison - Peng Q.; Buticchi G.; Tan N.M.L.; Guenter S.; Yang J.; Wheeler P. (Institute of Electrical and Electronics Engineers Inc., 2023)
Aircraft; Harmonic analysis; Power converters; Power electronics; Voltage control; Dynamic phasors model; Harmonic model; Harmonic state; Harmonic state-space; Linear time-periodic system; Model method; Power electronics converters; Pulse width modulation; Pulsewidth modulations (PWM); State-space; Pulse width modulation